The Bank of Japan's Monetary Policy Lacks a Strong Driving Force for Building Inflation Expectations: A Proposal for the Achievement of Labor-Management Agreement on Inflation Target of 2% and Base Wage Increases of 2%. (2nd July 2016) - Kitaura, Nobutoshi
Abstract : The Bank of Japan has been failing to create the 2% inflation expectations. This article presents the author's views about why the Bank of Japan's monetary easing measures have not led to achievement of the inflation target of 2%, as well as on measures required to achieve the 2% inflation (and base wage increases of over 3% which is the flip side of a 2% inflation). The major points of this article are outlined below. First, while many Japanese economists pay little attention to importance of mild inflation, the achievement of mild inflation of 2% is vital in ensuring a stable macroeconomic environment. Its achievement would enable lowering of real interest rates (i.e., reducing the real interest rate to minus 2% as against the 0% nominal interest rate) in the situation where the nominal interest rates are drifting at the lower limit against a backdrop of various economic shocks. It would also facilitate reduction in real wages against the downwardly rigid nominal wages, thereby helping companies revive their businesses, and also facilitating adjustments in the overall economy. Second, the reasons why the current Bank of Japan's monetary easing measures have been unsuccessful in attaining the inflation target of 2% are as follows: 1) most of the Japanese do not understand the importance of mild inflation and so the specific content of the inflation target (achieving 2% inflation and base wage increases of over 3%) is not clearly shared; 2) on top of the fact that deflation/zero inflation has become rooted in Japan's economy over the past two decades, Japan has never adopted a monetary policy that would anchor a mild inflation expectation of 2% (until 1990, the Bank of Japan's primary task was to be mindful of curbing the accelerating cost-push inflation associated with wage growth); and 3) the current Bank of Japan's monetary policy lacks a strong driving force for building inflation expectations to induce a change in people's behavior. Third, in order to build mild inflation expectations of 2% under such circumstances, it is important that the parties concerned with employer's associations and labor unions become fully aware of this target so that the 2% inflation and base wage increases of over 3% becomes a code of conduct. On that basis, the government and Bank of Japan need to clearly demand substantial base wage increases with concrete numerical targets combined with the achievement of mild inflation towards the goal of building inflation expectations. Fourth, I propose as the first step that, along with the economic measures recently taken, the government and the central bank either mediate or participate in a specific attempt to build a consensus between the employer's associations and labor unions on achieving, in a neutral manner, inflation of 2% and base wage increases of (at least) 2%. The aim is to establish an inflation of 2% and base wage increases of over 3% as a new code of conduct shared by employer's associations and labor unions through continued labor-management agreement. It is desirable that mild inflation is attained gradually by stimulating aggregate demand continuously, if time and cost permit and if the international environment tolerates weak yen. However, the current economic environment would not allow it and the leeway to ease monetary policy has also been limited. It is also difficult to continue to boost aggregate demand through fiscal policy in a sustained manner against a backdrop of a low birthrate and aging population. Although successful achievement of mild inflation is not a panacea for all economic problems, unless we first achieve mild inflation and restore the function of monetary policy, we will not be able to implement the subsequent structural reforms of the labor markets, etc. or fiscal consolidation, which are both painful. And thus, the long-term economic outlook of Japan is dismal. The author strongly hopes that the Abe Cabinet and Bank of Japan under the leadership of Governor Kuroda implements a drastic regime change similar to the one launched by the Roosevelt administration, overcome deflation and achieve mild inflation, restore the function of monetary policy at the earliest possible time, and get on the path to a true revitalization of the Japanese economy.